PERCEPTION OF HEPATITIS B AND ADULT HEPATITIS B VACCINATION: A PILOT STUDY AMONG MALAYSIAN HOUSEHOLDS USING MALAY VERSION QUESTIONNAIRE - Yogambigai Rajamoorthy; Niazlin Mohd Taib; Harapan Harapan; Subramaniam Munusamy; Alias Radam; Khalid Rahim (Malaysian Journal of Public Health Medicine, 2020)
Hepatitis B (HB) is an upcoming health issue in Malaysia. Even though the Expanded Programme on Immunisation (EPI) for HB vaccination implemented by the Malaysia government in 1989, individuals born before 1989 were not covered under the EPI and should immunised against the HB virus. Examining the Malaysians’ perception of vaccination is very important in order to determine their behaviour regarding HB vaccination. Most of the studies only gave priority to analysing this issue from an occupational risk perspective, consumers’ perceptions of the HB vaccination are still lacking. This study is aimed at assessing the validity and reliability of the Malay version of the perception questionnaire used for Malaysian households. A pilot study involving 300 respondents was conducted in six districts in the Selangor area. Factor analysis constructed four components: perceived sustainability, perceived severity, perceived benefit and perceived barriers loaded on the corresponding component with factor loading of more than 0.5. Principal component analysis of the finalised 13 items explained the instrument of the variance, which was 59.7% in total, 20.3%, 14.5%, 12.5% and 12.4% explained by the four constructs. The Cronbach alpha for the items instruments is 0.5 to 0.8 which shows that moderate internal consistency exists and demonstrates reliability of the questionnaire. The frequency of the four constructs shows that most of the respondents worry about getting infected with HBV, the perceived severity level is high among respondents, they perceived benefit from getting an HB vaccination and perceived low barriers to getting the HB vaccination.